The effect of social influence and platform reputation toward trust, investment intention, and actual investment on SMEs with peer-to-peer lending platform - Renny Soeta; Roy Sembel; Melinda Malau (Keynesia : International Journal of Economy and Business, 2023)
Most SMEs are funded by their own capital as they fall into the unbankable category. This is where financing services such as Peer to Peer (P2P) lending appear to be more flexible and faster in financing the capital needs of SMEs. This study is intended to examine the intention to invest in P2P lending platform specifically food sector of SMEs in Jakarta. 138 respondents from Jakarta were collected as potential investors through purposive sampling method using a questionnaire and processed furthermore using SPSS and SEM PLS. The research finds that social influence and reputation platform have a positive effect on trust. Meanwhile, trust has a positive effect on investment intention and investment intention has positive effect on actual investment. Moreover, if people already have the intention to invest, most likely they will do actual investment directly. The findings of this study will assist P2P platforms in enhancing their applications and marketing strategies to attract more investors, which will result in the funding of a greater number of SMEs businesses (SMEs), particularly in food industry.